KEANEKARAGAMAN JENIS AVIFAUNA DI CAGAR ALAM KELING II/III KABUPATEN JEPARA JAWA TENGAH - Chrystanto, Chrystanto; Asiyatun, Siti; Rahayuningsih, Margareta (Indonesian Journal of Conservation, 2014)
Nature Reserve (CA) Keling II / III is one of the nature reserves in Central Java which is impaired due to the local community use; therefore, the area does not function as it was initially planned. The aim of this study was to find out the diversity of avifauna or group of birds as information to determine management plans in that region. The observation method of Bird-watching applied point count and the data obtained were analyzed using the Shannon Wiener diversity index. The results showed 23 species of birds are found. They were from 6 orders and 14 families. A total of six listed were protected species as it was mentioned in government regulation No. 7 Year 1999 on the preservation of flora and fauna as well as the Law No. 5 Year 1990, namely Javan KingfisherÂ (Halcyon Cyanoventris), Collared Kingfisher (Halcyon Chloris), Javan Pond Heron (Ardeola Speciosa), Cattle Egrets (Bubulcus Ibis), Little Egret (Egretta Garzetta), And Olive-Backed Sunbird (Cinnyris Jugular). The Diversity Index (Shannon Wiener) in the region was 2.68.Keywords: Nature Reserves Keling II / III, Avifauna, DiversityÂ Cagar Alam (CA) Keling II/III merupakan salah satu cagar alam di jawa Tengah yang mengalami gangguan akibat pemanfaatan masyarakat sekitar, sehingga kawasan tersebut tidak berfungsi sebagaimana awal penunjukannya. Tujuan penelitian ini adalah mengetahui keanekaragaman avifauna atau kelompok burung sebagai informasi untuk menentukan rencana pengelolaan di kawasan tersebut. Metode pengamatan burung di lapangan menggunakan point count. Data pengamatan selanjutnya dianalisis dengan menggunakan indeks keanekaragaman Shannon Wiener. Hasil pengamatan menunjukkan ditemukan 23 spesies burung dari 6 ordo dan 14 family. Sebanyak enam spesies yang ditemukan tercatat dilindungi dalam peraturan pemerintah No.7 Tahun 1999 tentang pengawetan jenis tumbuhan dan satwa serta UU No 5 Tahun 1990 antara lain Halcyon cyanoventris (cekakak jawa), Cekakak sungai (Halcyon chloris) Blekok sawah (Ardeola speciosa), Kuntul kerbau (Bubulcus ibis), Kuntul kecil (Egretta garzetta), dan Cinnyris jugularis (burungmadu sriganti). Indeks Keanekaragaman (Shannon Wiener) di kawasan tersebut sebesar 2,68.Kata kunci : Cagar Alam Keling II/III, Avifauna, KeanekaragamanÂ